PERSEPSI GURU PADA PENDIDIKAN MULTIKULTURAL BERBASIS AGAMA DI SEKOLAH DASAR ISLAM TERPADU IQRA KOTA SERANG - Uyu Mu’awwanah; Arita Marini; Arifin Maksum (PGSD UNIKA SANTU PAULUS RUTENG, 2021)
Teachers tend to have less knowledge in the conceptualization of multicultural education. This study aims to determine teacher perceptions of religion-based multicultural education in integrated Islamic elementary school Iqra, Serang city. This study used a qualitative descriptive research method by collecting data through observation and interviews with teachers at the Islamic elementary school integrated Iqra, Serang city. In this study, it is revealed that multicultural education is implemented integrated in several subjects such as PPKn and Indonesian. This study recommends that multicultural education should be part of the curriculum in education. Teachers need to be given training on the implementation of multicultural education to provide teachers with an understanding of the practice of multicultural education in religion-based schools.